Dry Canal in Iraq and Mutual Growth in International Economic Environment - شهاب سلام جبار (Journal of Economics and Administrative Sciences, 2017)
In this paper, an attempt was made to measure and interpret the impact of several variables on global maritime transport, including: OECD industrial productions, high growth rates of some developing countries, and growth in world GDP. These variables contribute to higher rates of maritime transport revenues of 800 billion dollars annually; in the form of numerical sequences. The dry canal in Iraq was assumed to transfer 99 million tons of goods annually. This was made sure through the economic feasibility of the difference between maritime and land transport through railways. The effect of geographical and anthropological nature of Iraq on this project was studied too. Our findings indicated that the project will not drive growth in the global economy, but will have bilateral arrangements with high-growth countries such as China, India, Germany and Japan, etc. will have the important role of growth of the commodity sectors in these economies. Besides; strengthening the administrative and political unity of the country (Iraq), created an economic window for the federal budget that comes after the oil income, and decreased the imported prices of goods in Iraq and the region by 8%.